The relationship between organizational commitment, commitment to supervisor and servant leadership - Godbersen, Hendrik; Dudek, Bettina; Ruiz Fernández, Susana (Frontiers in Organizational Psychology, 2024)
The purpose of this study is to empirically establish which effects the facets of servant leadership have on the facets of commitment to supervisor and which effect the facets of commitment to supervisor have on the facets of organisational commitment. To this end, we conducted a survey with 1,756 participants, who roughly represent the German workforce by gender and age, to measure organisational commitment, commitment to supervisor and servant leadership. To test the relationship between the facets of the examined constructs, we analysed our data using partial least squares path modelling. Our results indicate that commitment to supervisor serves as a relevant, but not the only, antecedent of organisational commitment. Furthermore, our results indicate that affective and normative commitment to supervisor is relatively strongly affected by the servant leadership facets empowerment and stewardship, relatively moderately by forgiveness, authenticity and humility, and relatively weakly by standing back and accountability. Organisations are advised to prioritise the afore-mentioned facets of servant leadership in a corresponding order when selecting and developing managers as servant leaders.The results and findings of our study provide rather comprehensive insights in the complex relationships of organisational commitment, commitment to supervisor and servant leadership, which can serve as a basis for further research and assist the managerial practice.